ANALISIS PENGARUH VARIASI MASSA LPG SEBAGAI REFRIGERAN TERHADAP PRESTASI KERJA DARI LEMARI ES - Alfons Erick Perkasa; Nasrul Ilminnafik; Digdo Listyadi (Jurusan Teknik Mesin Fakultas Teknik Universitas Jember, 2013)
Refrigerant is a fluid acting on a cooling machine that plays an important role in a carnot cycle cooling engine. In study was done by looking at the effect of adding refrigerant mass variation of the COP (Coefficient of Performance) by using a refrigerant-based non-Freon refrigerant that use LPG (Petrileum Liquefied Gas). In this study using the LPG mass variations 50 grams, 80 grams and 90 grams and use R-12 refrigerant. From the research conducted, the results obtained from the performance engine cooling using refrigerant 80 grams times higher than that using the mass 50 grams and 90 grams, the highest coefficient of performance that is equal to 6,30 The result of research conducted, the result that the COP of the vapor compression machine (fridge) with a variation of the mass is the mass composition 80 grams is best used to obtain the greatest COP. Keyword : carnot’s siklus, COP (Coefficient of Performance), LPG(Liquefied Petrileum Gas)